2023
DOI: 10.1097/tp.0000000000004404
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role for Donor-specific Antibody Testing in Simultaneous Liver-kidney Transplantation: A Single-center Analysis of Outcomes

Abstract: Background. Simultaneous liver-kidney transplantation (SLKT) is increasingly used for patients with concurrent end-stage liver and renal disease. Emerging evidence suggests that simultaneous liver transplant can provide a tolerogenic benefit to multiorgan transplant recipients. Posttransplant donor-specific antibody (DSA) may be associated with worse outcomes; however, the role for testing DSA in SLKT is unclear. Methods. This study retrospectively assessed the impact of DSA on outcomes following primary SLK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Testing 'Donor specific antigen' (DSA) was one of the recommended tests in immunological screening in both living donor and deceased donor renal transplant. On the other hand, one study on simultaneous liver and kidney transplant (SLKT) involving 135 patients reported that SLKT is associated with excellent long-term patient and allograft survival with a relatively low rate of rejection; testing for DSA does not impact SLKT outcomes [16]. The point considered retrospectively was that 'it would be better to postpone the donor if ' AHG DTT B cell positive' in CDC cross match result'.…”
Section: Discussionmentioning
confidence: 99%
“…Testing 'Donor specific antigen' (DSA) was one of the recommended tests in immunological screening in both living donor and deceased donor renal transplant. On the other hand, one study on simultaneous liver and kidney transplant (SLKT) involving 135 patients reported that SLKT is associated with excellent long-term patient and allograft survival with a relatively low rate of rejection; testing for DSA does not impact SLKT outcomes [16]. The point considered retrospectively was that 'it would be better to postpone the donor if ' AHG DTT B cell positive' in CDC cross match result'.…”
Section: Discussionmentioning
confidence: 99%